Assembly mechanism of macroinvertebrate metacommunities and ecological factors of multiple aspects of beta diversity in a boreal river basin, China - Zheng, Biao; Yin, Xuwang (Frontiers in Ecology and Evolution, 2023)
The emergence of metacommunity theory has significantly contributed to our understanding of the drivers of community assembly and biome variation. The Network Location Hypothesis (NPH) posits that tributary communities situated at the source regions of a river are disproportionately susceptible to environmental filtering due to their remote location and consequent reduced connectivity to downstream reaches of the river system. However, downstream communities located in central parts of the river network exhibit increased connectivity to other communities, thereby making them more susceptible to spatial effects. Nonetheless, empirical studies testing this theory have been relatively scarce to date. Additionally, it is widely acknowledged that integrating multiple dimensions of beta diversity can enhance our understanding of the mechanisms driving community assembly. Based on the above, we collected macroinvertebrate samples from a boreal river in China to verify these views. Specifically, we examined the significance of network location on metacommunity assembly (NPH hypothesis) by utilizing a distance-decay relationship and simultaneously assessing multiple dimensions of ecological drivers of beta diversity. Our results revealed that the predictions of the NPH hypothesis were not supported in the study area, with the impact of environmental filtering on community assembly being prevalent regardless of network location. Taxonomic beta diversity consists almost entirely of turnover, with turnover contributing more to functional beta diversity than nestedness, while phylogenetic beta diversity consists of a combination of turnover and nestedness. We observed that a uniform species composition across sites led to higher taxonomic beta diversity in the study area. However, functional redundancy and the presence of closely related species across sites resulted in lower functional and phylogenetic beta diversity compared to taxonomic beta diversity. Although we found some correlation between phylogenetic and functional beta diversity, their mechanisms of variation were not consistent, with phylogenetic beta diversity showing greater variability than functional beta diversity. This suggests that differences in functional traits may be primarily driven by more distantly related species. Therefore, our findings do not fully support the use of phylogenetic distance as a surrogate for functional distance. The present study emphasizes the significance of incorporating multiple dimensions of beta diversity in metacommunity research, as they offer unique insights into beta diversity. Specifically, we found that environmental factors play a crucial role in shaping macroinvertebrate community composition and functional traits, which is associated with the higher environmental heterogeneity within the study area. In contrast, spatial processes, such as dispersal limitations, lead to variations in the evolutionary history of organisms across different locations, which is associated with the larger geographical extent of the study area.